Risk management in major sporting events: a participating national olympic team's perspective - Hanstad, D. V. (Event management, 2012)
This article explores the process of risk management in a major sporting event from the perspective of a participating team. More specifically, the article examines how Norway`s national team before and during the 2010 Olympic Winter Games (OWG) in Vancouver (i) identified the risk management issues, and (ii) handled risk strategies. The qualitative case study reported here draws upon documents and interviews with key actors in the Norwegian Top Sports Program (Olympiatoppen) and other important stakeholders for the preparation and implementation of the Vancouver project based on the experiences from 2006 OWG in Turin, Italy. The article utilizes previous research on risk management and strategic management in order to analyze a participating team`s preparation and implementation. A framework for dealing with risk management issues experienced by participating teams at sporting events is provided.